Pitch and Loudness Tinnitus in Individuals with Presbycusis - Seimetz,Bruna Macangnin (2016)
Abstract Introduction Tinnitus is a symptom that is often associated with presbycusis. Objective This study aims to analyze the existence of association among hearing thresholds, pitch, and loudness of tinnitus in individuals with presbycusis, considering the gender variable. Methods Cross-sectional, descriptive, and prospective study, whose sample consisted of individuals with tinnitus and diagnosis of presbycusis. For the evaluation, we performed anamnesis along with otoscopy, pure tone audiometry, and acuphenometry to analyze the psychoacoustic characteristics of tinnitus individuals. Results The sample consisted of 49 subjects, with a mean age of 69.57 6.53 years, who presented unilateral and bilateral tinnitus, therefore, a sample of 80 ears. In analyzing the results, as for acuphenometry, the loudness of tinnitus was more present at 0dB and the pitch was 6HKz and 8HKz. Regarding the analysis of the association between the frequency of greater hearing threshold and tinnitus pitch, no statistical significance (p= 0.862) was found. As for the association between the intensity of greater hearing threshold and tinnitus loudness, no statistical significance (p= 0.115) was found. Conclusion There is no significant association between the hearing loss of patients with presbycusis and the pitch and loudness of tinnitus.